Intercultural education for all? The education experience of indigenous children in three educational contexts (Revista Peruana de Investigación Educativa, 2012)
This qualitative research was conducted under the Young Lives project. The aim of this paper is to analyze how pertinent is the schooling experience of indigenous students for their linguistic and cultural characteristics. The methodology was based on a comparative case study in three public schools in the Ancash region. To study the adequacy of the school experience for students, we used three lines of analysis: the use of native language in the classroom, the incorporation of local knowledge in the curriculum, and the community involvement in schools. The findings lead us to argue that the school experience of these children does not meet their language and cultural needs, and community participation in education is restricted to the involvement of parents in economic and material requirements of the school.
Keywords: intercultural education; bilingual education; diversification of education; community participation